Protein kinase CK2-mediated phosphorylation of HDAC2 regulates co-repressor formation, deacetylase activity and acetylation of HDAC2 by cigarette smoke and aldehydes - Adenuga, David (2010)
Histone deacetylase 2 (HDAC2) mediates the repression of pro-inflammatory genes by deacetylating core histones, RelA/p65 and the glucocorticoid receptor. Reduced level of HDAC2 is associated with steroid resistant inflammation caused by oxidants. However, the molecular mechanisms regulating HDAC2 in response to oxidants and unsaturated aldehydes is not known. Here, we report that oxidative stress imposed by cigarette smoke extract (CSE), and aldehyde acrolein induced phosphorylation of HDAC2 which was abolished by serine-alanine mutations at serine sites S(394), S(411), S(422) and S(424). HDAC2 phosphorylation required direct interaction with serine-phosphorylated protein kinase CK2α and involved reduced HDAC2 deacetylase activity. Furthermore, HDAC2 phosphorylation was required for HDAC2 interaction with transcription factors, co-repressor complex formation, CBP recruitment, acetylation on lysine residues and consequently increased transrepression activity. Thus, phospho-acetylation of HDAC2 negatively regulates its deacetylase activity which has implications in steroid resistance in chronic inflammatory conditions.